2020
DOI: 10.1136/bmjdrc-2020-001343
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of patients with severe covid-19 with diabetes

Abstract: ObjectiveThis study explores the clinical characteristics of patients with diabetes with severe covid-19, and the association of diabetes with survival duration in patients with severe covid-19.Research design and methodsIn this single-center, retrospective, observational study, the clinical and laboratory characteristics of 193 patients with severe covid-19 were collected. 48 patients with severe covid-19 had diabetes, and 145 patients (ie, the controls) did not have diabetes. A severe case was defined as inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

73
497
8
48

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 495 publications
(626 citation statements)
references
References 34 publications
73
497
8
48
Order By: Relevance
“…According to the laboratory ndings, non-survivors had lower lymphocyte count and higher counts of WBC and neutrophil besides higher concentration of serum creatinine, CRP, LDH, CPK and CPK-MB, but lower concentration of Hb compared to survivors, re ecting severe in ammatory response and cardiac and renal impairments in nonsurvivors. Our ndings were in agreement with previous observations in COVID-19 patients [11,[15][16][17]. These biochemical abnormalities point to that covid-19 infection may be lead to progressive systemic injuries and consequently death in diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to the laboratory ndings, non-survivors had lower lymphocyte count and higher counts of WBC and neutrophil besides higher concentration of serum creatinine, CRP, LDH, CPK and CPK-MB, but lower concentration of Hb compared to survivors, re ecting severe in ammatory response and cardiac and renal impairments in nonsurvivors. Our ndings were in agreement with previous observations in COVID-19 patients [11,[15][16][17]. These biochemical abnormalities point to that covid-19 infection may be lead to progressive systemic injuries and consequently death in diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
“…These biochemical abnormalities point to that covid-19 infection may be lead to progressive systemic injuries and consequently death in diabetic patients. The mechanisms linking diabetes with high risk of mortality were pulmonary dysfunction and deleterious in ammation which has been indicated in results of comparison between survivors and non-survivors [15,18]. Chen et al indicated CRP as the only risk factor for mortality in diabetic patients with COVID-19 as a clinical manifestation of systemic in ammation [19].…”
Section: Discussionmentioning
confidence: 99%
“…In this study which had relatively rich clinical data, we found that diabetes alone was not the independent risk factors for in-hospital mortality of COVID-19, but comorbidities such as hypertension, CKD were risk factors, this result was consistent with the previous study [13]. Partially consistent with the previous studies, our study found that, compared with non-diabetic patients, diabetic COVID-19 patients were older, had worse outcome including higher rate of mortality, severe cases and ARDS, presented severe in ammation response, lung and coagulation dysfunction [2,11,12,14]. Additionally, diabetic patients had increased level of urea nitrogen and decreased level of albumin.…”
Section: Discussionsupporting
confidence: 91%
“…Lots of studies had demonstrated that diabetic patients had higher risk of mortality in COVID, as well as developing more severe cases [2,4,11,12]. Guo et al [12] reported that diabetes was a risk factor for the progression and prognosis of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Why is diabetes associated with severe covid-19 lung disease requiring admission to the ICU? In a report in this journal, Yan et al 13 Editorial with severe covid-19 without diabetes hospitalized in China in a retrospective single center observational study. The authors demonstrate that compared with non-diabetics, patients with diabetes and severe covid-19 exhibited a severe inflammatory response and were more likely to receive mechanical ventilation and have a higher mortality (and a reduced survival duration).…”
mentioning
confidence: 99%